2001
DOI: 10.2337/diabetes.50.12.2682
|View full text |Cite
|
Sign up to set email alerts
|

Physiologic Hyperinsulinemia Enhances Human Skeletal Muscle Perfusion by Capillary Recruitment

Abstract: Despite intensive study, the relation between insulin's action on blood flow and glucose metabolism remains unclear. Insulin-induced changes in microvascular perfusion, independent from effects on total blood flow, could be an important variable contributing to insulin's metabolic action. We hypothesized that modest, physiologic increments in plasma insulin concentration alter microvascular perfusion in human skeletal muscle and that these changes can be assessed using contrastenhanced ultrasound (CEU), a vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
210
1
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 219 publications
(231 citation statements)
references
References 55 publications
16
210
1
2
Order By: Relevance
“…The present results are in agreement with previous studies that have demonstrated insulin-mediated effects on microvascular perfusion in human muscle using positron emission tomography or contrastenhanced ultrasound [6,7]. However, these methods do not measure muscle perfusion in real time and are therefore not able to measure vasomotion.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The present results are in agreement with previous studies that have demonstrated insulin-mediated effects on microvascular perfusion in human muscle using positron emission tomography or contrastenhanced ultrasound [6,7]. However, these methods do not measure muscle perfusion in real time and are therefore not able to measure vasomotion.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, iontophorised insulin can directly increase skin microvascular perfusion, indicating a direct local microvascular effect of insulin [8]. Moreover, animal and human studies suggest that insulin-induced changes in basal microvascular perfusion occur before changes in total blood flow demonstrating an independency of both phenomena [5,7,27].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…1 Values are means±SE for n=8 in each group *p<0.05 difference from saline; # p<0.05 difference from insulin contrast, there is growing evidence that insulin-mediated capillary recruitment may play a key role in muscle glucose uptake, particularly in animal models [18] and is impaired in animal models of muscle insulin resistance [12][13][14]41] and in obese humans [42,43]. Capillary recruitment is controlled independently of limb blood flow [17,18,21] and occurs in response to locally administered physiological insulin in human forearm in association with glucose uptake [44]. In the absence of an endothelial involvement, insulin may act directly on vascular smooth muscle cells of the terminal arterioles to mediate capillary recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the present studies, the heart rate and blood pressure were normal and other recent studies have shown that insulin-mediated capillary recruitment occurred early, relative to muscle glucose uptake [18] and at physiological doses of insulin [17], indicating that a desensitising effect of the anaesthetic is unlikely. Moreover, studies in human forearm, where the subjects were instructed to remain still, have shown insulin-mediated capillary recruitment, again at physiological insulin levels [44].…”
Section: Discussionmentioning
confidence: 99%